New porous monolithic membranes based on supported ionic liquid-like phases for oil/water separation and homogenous catalyst immobilisation. Issue 19 (19th February 2018) - Porcar, Raúl; Nuevo, Daniel; García-Verdugo, Eduardo; Lozano, Pedro; Sanchez-Marcano, José; Burguete, M. Isabel; Luis, Santiago V.
Abstract : Membranes based on supported ionic liquid-like phase (SIILP) systems with tunable properties allowed oil/water separation and reaction/separation integration in biphasic systems. Abstract : Porous monolithic advanced functional materials based on supported ionic liquid-like phase (SILLP) systems were used for the preparation of oleophilic and hydrophobic cylindrical membranes and successfully tested as eco-friendly and safe systems for oil/water separation and for the continuous integration of catalytic and separation processes in an aqueous–organic biphasic reaction system.